Oxidative Stress, Physiological Responses and Performance of Broilers Transported with Different Transportation Duration - Wicaksono, M. A.; Afnan, R.; Suryati, T. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2020)
Transportation plays important factor in broiler industry. Whole transportation process from loading tounloading can cause stress to broilers. The duration of the trip can affect oxidative stress, physiologicaland performance of broiler. This study aim to evaluate the effects of different transportation durationson oxidative stress, physiological responses and performance of broilers. Transportation from farm toslaughterhouse using a truck with a capacity of 144 crates. There were two durations treatment in this study,180 and 240 mins. Variables measured in this study were oxidative stress indicators (malondialdehyde/MDA content and catalase enzyme activity), physiological responses (rectal temperature and heterophilelymphocytes (HL) ratio), and performance represented by weight loss percentage. Normality test wasdone before T Test. Data analyzed using T Test independent which compared data between before andafter transportation. T Test dependent which compared data between short and long duration. The resultshowed that duration of transportation significantly affects on decrease liver and thigh catalase enzymeactivity, decrease malondialdehyde value on liver, decrease HL ratio after transportation, differenceson rectal temperature and weightloss. Long transportation duration resulted the lowest liver and thighcatalase enzymes activity (0.097±0.023 and 0.088±0.014 U/mL). It can be concluded that the long durationtransportation catalase enzyme activity reduce MDA value and affected performance indicator